2011
DOI: 10.1177/1358863x11404940
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of firefighting on arterial stiffness and blood flow

Abstract: Sudden cardiac events are responsible for 40-50% of line-of-duty firefighter fatalities, yet the exact cause of these events is unknown. Likely, combinations of thermal, physical, and mental factors impair cardiovascular function and trigger such events. Therefore, the purpose of this study was to examine the impact of firefighting activities on vascular function. Sixty-nine young (28 ± 1 years) male firefighters underwent 3 hours of firefighting activities. Carotid, aortic, and brachial blood pressures (BP), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 45 publications
3
56
1
Order By: Relevance
“…3,26 This cardiovascular strain typically manifests as markedly elevated HR 3,4,15,[27][28][29] that results in increased RPP and myocardial work. Consistent with previous literature, our findings illustrate significant cardiovascular strain following EIHS compared to NHS.…”
Section: Discussionmentioning
confidence: 99%
“…3,26 This cardiovascular strain typically manifests as markedly elevated HR 3,4,15,[27][28][29] that results in increased RPP and myocardial work. Consistent with previous literature, our findings illustrate significant cardiovascular strain following EIHS compared to NHS.…”
Section: Discussionmentioning
confidence: 99%
“…They also reported that treatment with vitamin C had no effect on these hemodynamic and vascular parameters when compared to a placebo. 6 In our study, we found that exercise in thermal protective clothing resulted in a transient non-significant increase in AI followed by a significant drop in AI at 90 minutes after exertional heat stress. Additionally, we observed a beneficial effect of daily low-dose aspirin on peripheral arterial stiffness, but not on endothelial function, before and after exertional heat stress.…”
Section: Discussionmentioning
confidence: 70%
“…6 Among 69 volunteer and career firefighters, Fahs and colleagues observed increases in aortic diastolic blood pressure, heart rate, AI, pulse wave velocity and RHI, and significant decreases in brachial and aortic pulse pressure following firefighting activities. They also reported that treatment with vitamin C had no effect on these hemodynamic and vascular parameters when compared to a placebo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations